Hubungan Hardiness dan Adaptabilitas Karir Pada Mahasiswa Tingkat Akhir - Pasangkin, Femi; Huwae, Arthur (Universitas PGRI Madiun, 2022)
Adulthood has an important role in a career. However, individuals often make mistakes in designing and making career choices. Determining and preparing for a career are usually experienced by final year students in college. In preparing for a career, individuals need to have career adaptability so that they are able to determine the career achieved, be confident about the career achieved, and be able to overcome obstacles in a career. Therefore, this study aims to determine the relationship between hardiness and career adaptability in final year students. The type of research method used is quantitative with a correlational design. The participants involved in this study were 165 people spread throughout Indonesia. The measurement scale used is a hardiness scale and a career adaptability scale. The results based on the product moment-Pearson correlation test, r = 0.661 with sig. = 0.000 (p<0.01). From the results of the study, it can be concluded that there is a significant relationship between hardiness and career adaptability in final year students. So, the hypothesis proposed in this study can be accepted